Hubungan Hygiene dan Sanitasi dengan Kejadian Penyakit Diare pada Siswa SD Gmim Sonder Tahun 2025 - Jeliny V. Mondigir; Theo. W. E. Mautang; Nancy S. Bawiling (Yayasan Syalom Cipta Sumikolah, 2025)
The food consumed must be safe in the sense of being free from physical, chemical, and microbiological contaminants. The mortality rate is still quite high (1%) compared to the Case Fatality Rate (CFR) during outbreaks which was 0.40% in 2011, and the CFR in 2018 increased to 4.76% compared to 2017 (Ministry of Health of the Republic of Indonesia, 2019). The causes of diarrhea in individuals cannot be separated from the healthy living habits of each family and the unhealthy environmental sanitation. It can be concluded that the occurrence of diarrhea is influenced by environmental factors, including access to clean water, home health conditions, and handwashing habits. This research is a study with a quantitative descriptive approach. The number of samples to be studied is 61 students. The research was conducted on May 25, 2025. There is a statistically significant relationship between defecation behavior and the occurrence of diarrhea (p 0.043). There is a significant relationship between snack behavior and the occurrence of diarrhea (p 0.041). There is a significant relationship between handwashing behavior and the occurrence of diarrhea (p 0.043). A significant relationship was found between nail cleanliness behavior and the occurrence of diarrhea (p 0.029). Overall, although some results indicate a significant relationship between clean living behavior and the incidence of diarrhea, some emerging patterns actually suggest trends that are contrary to theoretical expectations. This indicates that diarrhea prevention must be carried out comprehensively, not just focusing on one aspect of behavior, but rather integrating all good hygiene practices.